Meta analisis Video Pembelajaran dalam Menghadapi Tantangan Pendidikan di Era Revolusi Industri 4.0 - Novisya, Dira; Festiyed, Festiyed (Jurnal Penelitian Pembelajaran Fisika, 2019)
The ability to learn in the 4.0 revolution is still worrying. the lack of professional teachers to improve student needs, the learning system implements LOTS learning instead of Hots, the lack of teachers using IT in learning. The use of media is still simple. The method used is a meta-analysis of quantitative approaches through the calculation and analysis of data already in the article. The number of samples taken using six articles related to video from 2013-2018. Data analysis was performed using the sice effectuses a meta-analysis of four articles related to video. the number of samples taken using four articles starting from 2013-2017. Analytical techniques that use a quantitative approach effect sizes. from the video results obtained 1.47 with a very high category. the video had a major impact on students' heutagogy in learning physics